2011
DOI: 10.1159/000328448
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Keratin 19 Is Related to High Recurrence of Hepatocellular Carcinoma after Radiofrequency Ablation

Abstract: Objective: Keratin (K) 19 positivity has been reported to be a useful predictive marker for recurrence in patients with hepatocellular carcinoma (HCC) who have undergone hepatic resection. We investigated the clinical usefulness of K19 positivity in patients who had received curative radiofrequency ablation (RFA). Methods: We retrospectively evaluated the clinicopathological features, including imaging and K19 expression, in 246 patients with HCC who were within the Milan criteria and had received curative RFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 53 publications
(42 reference statements)
3
54
1
Order By: Relevance
“…Despite the possible overestimation or underestimation of protein expression, we confirmed the prognostic value of K19 expression in diagnostic needle biopsies. 4 In this study, EPCAM did not prove to have the same prognostic value as K19. This could be explained by the fact that in regenerating liver, EPCAM is a much broader marker than K19, as it also marks the progeny of the HPCs, the intermediate hepatocytes, similar to K7.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Despite the possible overestimation or underestimation of protein expression, we confirmed the prognostic value of K19 expression in diagnostic needle biopsies. 4 In this study, EPCAM did not prove to have the same prognostic value as K19. This could be explained by the fact that in regenerating liver, EPCAM is a much broader marker than K19, as it also marks the progeny of the HPCs, the intermediate hepatocytes, similar to K7.…”
Section: Discussioncontrasting
confidence: 57%
“…[2][3][4][5][6] In 2006, our group was the first to describe the clinicopathological and prognostic relevance of K19 in a Caucasian series of HCCs as it was linked with a high recurrence after transplantation. 7 Subsequently, we started a prospective study on a Caucasian series of 242 consecutive HCC samples with a different range of aetiologies and performed a detailed evaluation of the clinicopathological relevance of K19.…”
Section: What Are the New Findings?mentioning
confidence: 99%
“…As K19 and/or K7-positive HCC cells were not diffusely present in this study, the expression frequencies in the 3 mm TMA core may have been underestimated. This hypothesis was supported by a recent study which demonstrated that K19 expression in biopsy specimens for HCC taken prior to radiofrequency ablation is extremely low (4.1%) (8). Assessment of a biomarker in a small TMA tissue core may not accurately reflect the assessment that would be obtained from a whole section analysis due to intratumoral heterogeneity (30).…”
Section: Discussionmentioning
confidence: 92%
“…K19 expression in HCC is associated with recurrence, metastasis and poor prognosis (5)(6)(7)(8). Recent studies have postulated that K19-positive HCCs originates from hepatic progenitor cells (HPCs) (5,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…As for curatively treated HCC patients, tumor differentiation or progenitor-cell feature markers of cancerous tissue have been identified as predictors of recurrence [13,14]. In contrast, only several reports have mentioned the importance of background noncancerous liver tissue and the microenvironment; these are predictive of HCC recurrences [15,16].…”
Section: Introductionmentioning
confidence: 99%